2011
DOI: 10.1590/s1809-98232011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de enteroparasitos em idosos

Abstract: OBJETIVOS: Avaliar a prevalência de parasitos intestinais em idosos que frequentam um ambulatório geriátrico de Porto Alegre, no Rio Grande do Sul (RS), e moradores de duas instituições de longa permanência (ILP) do mesmo município. Analisar a presença de enteroparasitos nos animais de estimação desses idosos. METODOLOGIA: O exame parasitológico das fezes (EPF) foi feito para diagnosticar a presença de parasitos nas fezes dos idosos e dos animais de estimação. Os métodos utilizados para a avaliação dos parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
19

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 11 publications
0
9
0
19
Order By: Relevance
“…International studies have found a prevalence of 37.7% in the elderly who visited a medical center in Santiago, Chile, 8 and 26.5% among elderly patients at a hospital in Costa Rica. 11 However, more recent studies have identified a lower prevalence in the institutionalized elderly: 12.9% in Porto Alegre, Rio Grande do Sul, 9 and 9.5% in Uberlândia, Minas Gerais. 3 These differences in prevalence may occur due to the socioeconomic and environmental differences between the studied populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies have found a prevalence of 37.7% in the elderly who visited a medical center in Santiago, Chile, 8 and 26.5% among elderly patients at a hospital in Costa Rica. 11 However, more recent studies have identified a lower prevalence in the institutionalized elderly: 12.9% in Porto Alegre, Rio Grande do Sul, 9 and 9.5% in Uberlândia, Minas Gerais. 3 These differences in prevalence may occur due to the socioeconomic and environmental differences between the studied populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported cases in certain areas where the prevalence of intestinal parasitic infections in elderly population ranges from 9.5% to 72.8%. 3,[7][8][9][10][11] To understand the reality and needs of each region, the Family Health Strategy (FHS) team, which is part of the Unified Health System in Brazil, implements health surveillance, promotion, prevention, and disease control activities. 12 The use of epidemiological tools and the collection of survey data by Community Health Workers (CHW) regarding the social and environmental factors that may affect human health enable closer proximity of health services to the population.…”
Section: Introductionmentioning
confidence: 99%
“…Endolimax nana and E. coli were the most frequent commensal infections. [18][19][20] Entamoeba histolytica/dispar is one of the most prevalent infections in the Amazon region. 21 In the southeast region of…”
Section: 29mentioning
confidence: 99%
“…This test in addition to its diagnostic contributions serves studies like this one provide epidemiological data that contribute to the improvement of health services, enabling the selection of appropriate forms of intervention for the control of these parasitoses [2].…”
Section: Discussionmentioning
confidence: 99%
“…Among the pathogenic helminths investigated, the one most often diagnosed is Strongyloides stercoralis (S. stercoralis), a nematode parasite that causes strongyloidiasis, a disease characterized by skin and digestive symptoms, in humans [1][2][3][4][5]. Parasitological surveys using more sensitive and rigorous techniques are needed to provide more reliable results and serve as the basis for future interventions involving sanitary and educational measures to improve health maintenance [2]. In this sense, research carried out for the refinement of techniques applied to the epidemiological survey to parasitic diseases, such as the strongyloidiasis, is necessary.…”
Section: Introductionmentioning
confidence: 99%